The Concept of Conspiring to Corrupt in Criminal Law as Ius Contituendum - Yulianto Yulianto (Universitas Airlangga, 2019)
The term conspiring to commit criminal acts in Article 15 of PTPK Act cannot refer to existing norms under Article 88 of the KUHP. The criminal act which is to conspire to commit such acts within PTPK Act has been regulated within the Indonesian legal system and recognized by law enforcers. However, the lack of elaboration and clarity towards this type of criminal act in the PTPK Law has hindered law enforcers from utilizing Article 15 of the PTPK Act to combat corruption. The Constitutional Court has attempted to resolve the legal uncertainty of Article 15 of the PTPK Act, however this has been proven to become burdensome for law enforcers in applying the criminal justifications of conspiracy under the scope of Article 15 of the PTPK Act. The criminal act which is to conspire to commit such acts within PTPK Act has been regulated within the Indonesian legal system and recognized by law enforcers.